Genetic mutation analysis of hereditary spastic paraplegia: A retrospective study. Issue 23 (5th June 2020) - Cui, Fang; Sun, LiuQing; Qiao, Jie; Li, JianYong; Li, Mao; Chen, SiYu; Sun, Bo; Huang, XuSheng
Abstract : Abstract: Hereditary spastic paraplegias are heterogeneous disorders with diversified clinical manifestations, and genetic testing is important for the diagnosis and typing of hereditary spastic paraplegias. Gene panel sequencing containing 55 hereditary spastic paraplegias-related genes was performed to screen the pathogenic genes for hereditary spastic paraplegias. Sanger sequencing was adopted to validate if the family member carried the same pathogenic gene as the proband. Fifteen out of 53 patients carried mutation(s) in the screened hereditary spastic paraplegias-related genes. Among the 23 identified mutations, only one mutation had been previously reported as a pathogenic mutation. In the pedigree of case 6, the proband, his mother and uncle all carried the same novel deletion mutation (c.1459delA) at SPAST gene. Based on the pedigree, the disease was inherited in an AD pattern. In the pedigree of case 53, the family disease may be in an X-linked recessive inheritance pattern. The proband (case 53) carried two novel mutations in ALT1 gene and L1CAM gene (c.2511C>A), respectively. The L1CAM gene is the causative gene for the SPG1 X-linked recessive—hereditary spastic paraplegias. Our data confirm the genetic heterogeneity of hereditary spastic paraplegias, and SPG4/SPAST were the most frequent forms. The pathogenicity of the novel mutations is worth to be further investigated.